Measles in the Child: Clinical Case - Andrey Yu. Nikiforov; Tatiana L. Kostyukova; Svetlana Yu. Nagaeva; Anatoly F. Vinogradov; Lyubov P. Sizhenkova ("Paediatrician" Publishers LLC, 2020)
Background. Measles is a highly contagious viral infectious disease with airborne transmission. European countries has registered an increased incidence of measles during the period of 2018-2019 followed by the increased risk of epidemiological situation aggravation in Russia. Cases of measles in Russia are recorded mainly among unvaccinated persons who have refused to vaccinate, who have not been vaccinated due to medical contraindications and among homeless people.Clinical Case Description. Clinical case of the unvaccinated child with measles is presented. The disease had a severe course with a long-term fever, significant toxic syndrome and development of one of the most frequent complication - acute laryngotracheitis.Conclusion. The importance of implementation of prophylactic measures for prevention of measles emergence and spreading is specified, and the main approach is immunization of the population.